System of National Accounts, 1993. (International Monetary Fund, 1993)
The 1993 SNA represents a major advance in national accounting. While updating and clarifying the 1968 SNA, the 1993 SNA provides the basis for improving compilation of national accounts statistics, promoting integration of economic and related statistics, and enhancing analysis of economic developments. The 1993 SNA deals more clearly with relationships between economic flows (such as production, income, savings, accumulation, and financing) and links between these flows and stocks. At the same time the 1993 SNA reflects the many significant developments that have taken place in financial markets and completes the integration of balance sheets into the system. The 1993 SNA also suggests how satellite accounts (e.g. environmental accounts) and alternative classifications (e.g., through social accounting matrices) an be used to augment the central framework of the system.